The use of Cake application in improving English speaking skills of students SMPN 2 Kulo - Muh. Sinul Haq; Sam Hermansyah; Syahril L; Isumarni Isumarni (Universitas Muhammadiyah Enrekang, 2025)
Using the Cake application program, this study attempts to ascertain whether class VIII B students at SMPN 2 Kulo have improved their speaking correctness, particularly in their pronunciation. Pre-experimental research using a quantitative design was employed in this study to analyze data. A speaking exam with a pre-, treatment-, and post-test was the tool utilized. All SMPN 2 Kulo pupils made up the population, and class VIII B, which was chosen through selective selection, was the sample. Twelve pupils were enrolled in total.The results of the study demonstrated that students' speaking abilities were significantly impacted by the usage of cake applications to enhance speaking abilities, particularly in the area of pronunciation. This is demonstrated by the fact that students' average speaking accuracy score, particularly in pronunciation, was 66.08 on the pre-test and rose to 80.92 on the post-test. Furthermore, the t-test value (14.791 > 2.144) is greater than the t-table. This indicates that there is a rise in the use of cake applications to enhance pupils' speaking abilities, particularly with regard to pronunciation.